Presenting the internal evaluation model on the performance of the banking industry based on the data theory method of the foundation - Zahra Ramzanpour Osmavandani; mehdi Rouholamini; Shahrbanoo Gholipour (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to provide a model of the impact of internal marketing on the performance of the banking industry based on the data-based theory method. The research method is applicable in terms of the purpose, and qualitative in terms of the implementation method, based on the inductive approach. The statistical population of the research includes 8 experts of the banking industry, and the sampling was done in a targeted manner and the interviews continued until reaching theoretical saturation. Semi-structured interview was used in this research. To collect and analyze the data, the foundation's data theory research strategy was used. For data analysis, MAXQDA 2020 software was used to code the interviews. The results indicated that a total of 5 components of job security, training, employee motivation and satisfaction, positive communication, development and reward were identified as internal marketing features in the banking industry, and 14 components were identified and extracted in the form of causal conditions (establishing constructive interaction between employees and managers, generous rewards, employee empowerment, management support), foundational conditions (organizational leadership and management, human resource management measures, organizational culture), interventions (political climate, organizational costs), strategies (promotion of customer-oriented culture, person-job fit), and outcome (human development, value creation, increased commitment). Extended Abstract Introduction With the increasing demand for banking services in the society and the competition to maintain the interests of the country's banks, especially in the private banks, each bank, in some way or other, tries to attract people as customers within their financial system in order to benefit from the resulting benefits. Therefore, the success of all banks, governmental or non-governmental, is influenced by several factors; one of the most important of which is customer satisfaction, in order to achieve excellence in business; and this customer satisfaction is one of the basic requirements of quality management systems (Akbari, 2019). An important issue in marketing management is the relationship between internal marketing and business success; internal marketing as a construct or concept is not universally accepted. One of the key features of internal marketing is its connection with the performance of the organization (Tahmasbi et al, 2019). In the banking industry, the role of human capital in providing services is quite significant. Employees in this industry facilitate the implementation of the organization's strategies and superior performance through effective interaction with customers. Therefore, the solution to guarantee the excellent performance of the organization should be sought in the successful activation of human capital; and in order to achieve the goal of providing productive financial resources for the organization, the work should start by paying attention to the employees, that is, those who interact with customers and take care of their affairs. In this aspect of the activity of service organizations, the issue of internal marketing is raised (Naami & Mazhari, 2014). Based on this, the current research is looking for an answer to this question: What is the model of the effect of internal marketing on the performance of the banking industry based on the data-based theory method?